Primary screening of the bioactivity of brackishwater cyanobacteria: toxicity of crude extracts to artemia salina larvae and paracentrotus lividus embryos - Lopes, Viviana (2013)
Cyanobacteria are a diverse group of Gram-negative bacteria that produce an array of secondary compounds with selective bioactivity against vertebrates, invertebrates, plants, microalgae, fungi, bacteria, viruses and cell lines. The aim of this study was to assess the toxic effects of aqueous, methanolic and hexane crude extracts of benthic and picoplanktonic cyanobacteria isolated from estuarine environments, towards the nauplii of the brine shrimp Artemia salina and embryos of the sea urchin Paracentrotus lividus. The A. salina lethality test was used as a frontline screen and then complemented by the more specific sea urchin embryo-larval assay. Eighteen cyanobacterial isolates, belonging to the genera Cyanobium, Leptolyngbya, Microcoleus, Phormidium, Nodularia, Nostoc and Synechocystis, were tested. Aqueous extracts of cyanobacteria strains showed potent toxicity against A. salina, whereas in P. lividus, methanolic and aqueous extracts showed embryo toxicity, with clear effects on development during early stages. The results suggest that the brackishwater cyanobacteria are producers of bioactive compounds with toxicological effects that may interfere with the dynamics of invertebrate populations.